2013
DOI: 10.1021/es401643e
|View full text |Cite
|
Sign up to set email alerts
|

Aqueous Cu(II)–Organic Complexation Studied in Situ Using Soft X-ray and Vibrational Spectroscopies

Abstract: In situ aqueous solutions containing copper-ligand mixtures were measured at the Cu L-edge using X-ray absorption near edge structure (XANES) and with attenuated total reflectance infrared (ATR-FTIR) spectroscopies. Copper complexation with environmentally relevant ligands such as EDTA, citrate, and malate provided a bridge between spectroscopic studies and general environmental behavior and will allow for future study of complex environmental samples. XANES results show that the lowest unoccupied molecular or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…A recent publication on Cueligand complexation by Phillips et al (2013) using the SGM liquid cell is a good case study for how liquid Ledge measurements have great potential for environmental biogeochemical research. Copper (as Cu 2þ ) is a trace micronutrient that is essential for life at low levels but can become toxic at higher levels.…”
Section: Soft X-ray Liquid Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent publication on Cueligand complexation by Phillips et al (2013) using the SGM liquid cell is a good case study for how liquid Ledge measurements have great potential for environmental biogeochemical research. Copper (as Cu 2þ ) is a trace micronutrient that is essential for life at low levels but can become toxic at higher levels.…”
Section: Soft X-ray Liquid Cellsmentioning
confidence: 99%
“…It was found that long-term manure application produced C and N which were chemically stabilized compared to fertilization with synthetics or in a legume rotation. Finally, Phillips et al (2013) used a liquid cell analysis for a fundamental description of coppereligand chemistry. In this study, they showed that LUMO energy is governed by the ligand field strength and is related to Lewis acid/base properties of the ligand functional groups.…”
Section: Current Applications and Future Prospectsmentioning
confidence: 99%
“…When the potential reaches to the electro-reduction potential of CitÀ Cu ion at À 0.35 V, it can be discovered that three upward peaks appear at 1308, 1408 and 1558 cm À 1 . Phillips and Zabiszak et al [37,38] both reported that the peaks at 1325, 1430 and 1587 cm À 1 were attributed to the γ(CH 2 ), 1(COO) and γ(COO) of Cit molecule. Jastrzab et al [39] reported that the wavenumber of metal coordination ion would be shifted relative to that of coordination agent molecule.…”
Section: In Situ Ftir Analysis On the Adsorptions Of Enà Cu And Cità ...mentioning
confidence: 99%
“…The design of the electrochemical flow cell was adapted from a previously used flow cell. 41 Silicon nitride membrane windows (1 mm x 1 mm x 100 nm)…”
Section: Sample Cellmentioning
confidence: 99%